EFFECTIVENESS OF TUBERCULOUS RECOMBINANT ALLERGEN SKIN TESTS FOR DETECTING TUBERCULOSIS IN CHILDREN AND ADOLESCENTS OF MOSCOW IN 2013 - L. V. Slogotskaya; O. Y. Senchikhina; G. V. Nikitina; E. M. Bogorodskaya (Педиатрическая фармакология)
Explanation. Mantoux test is used to detect the tuberculous infection; however, low specificity of this method results in a high rate of false positive responses due to cross-reactions of PPD (protein purified derivate) antigens contained in many mycobacterial species and Bacillus Calmette-Guerin (BCG) strains. New drug Diaskintest (DST) — recombinant protein CFP10-ESAT6 produced by Escherichia coli BL21(DE3)/pCFP-ESAT proved to be the best acceptable diagnostic drug. The article was aimed at studying effectiveness of tuberculous recombinant allergen tests for detecting tuberculosis in the children and adolescents, who were registered in Moscow in 2013. Methods. Mantoux tests were used to examine 1,420,100 persons; positive reactions were observed in 1,020,000 children and adolescents (71,8%); 131,361 (12.9%) of them were examined using DSTs. Results. Positive reactions to DST were observed in 3,304 persons (2.5% of the persons with positive reactions to Mantoux test). The tuberculosis detection rate among the persons with positive reactions to Mantoux tests using 2TU PPD-L (Leningrad Research Institute of Vaccines and Serums) is 0.13%, among the persons with positive reactions to DSTs — 4.9%, i.e. 40 times more often (p = 0.000). Post-tuberculosis alterations were detected in 169 persons: in 0.13% of the persons with positive reactions to Mantoux tests using 2TU PPD-L and in 5.1% of the persons with positive reactions to DSTs (p = 0.000). Conclusion. Cohort studies conducted in Moscow demonstrated high effectiveness of Diaskintests for detecting tuberculosis in children and adolescents. High sensitivity of the method helps to detect the overwhelming majority of the persons with tuberculosis.